Effect of planting distances on the growth and productivity of mung bean (Vigna radaita L.) varieties in southern Iraq - Yasseen Muhsin Ghedyib (University of Thi-Qar Journal of agricultural research, 2024)
A field experiment during the fall season of 2023, it was conducted at the Agricultural Research Station affiliated to the College of Agriculture / University of  Basra in the Garmat Ali area, north of Basra Governorate (latitude 30.57 north and longitude 47.80 east)) with the aim of knowing the effected of three planting distances(20, 25, 30 cm in growth , yield and quality of four genotypes of mung bean crop (local, Omrani, parto, Gohar). A factorial experiment was applied according to the arrangement of split_split plots using a randomized complete block design (R.C.B.D) with three replicates where the planting distances occupied the main plots and the varieties occupied the secondary plots (sub-plot).       The results of statistical analysis of the data showed the significant effect of the varieties on the study traits, as the V4 variety outperformed in most of the traits that included plant height, number of branches, number of leaves, leaf area and leaf area index, and achieved the highest seed yield of 1.583 tons ha1 and the highest percentage of protein in the seeds of 23.392%.      The results also showed that the 20 cm planting distance was superior in plant height, leaf area, leaf area index and achieved the highest seed yield of 1.708 tons/ha. While the interaction between the V4 variety and the 20 cm planting distance achieved the highest average number of leaves and leaf area, the interaction between the V4 variety and the 25 cm planting distance achieved the highest percentage of protein in the seeds, reaching 624.30%.